2012
DOI: 10.1136/gutjnl-2012-302448
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive screening of chymotrypsin C (CTRC) gene in tropical calcific pancreatitis identifies novel variants

Abstract: This study on a large cohort of TCP patients provides evidence of allelic heterogeneity and confirms that CTRC variants play a significant role in its pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 25 publications
0
52
0
Order By: Relevance
“…It has been reported that the CTRC variants in exons 3 and 7 are associated with CP in Europe and India (Rosendahl et al 2008;Masson et al 2008;Beer et al 2013;Paliwal et al 2013). In European cohorts, the micro-deletion variants p.K247_R254del (c.738_761del24) and p.R254W, both located in exon 7, are the most common CTRC variants (Rosendahl et al 2008;Masson et al 2008;Beer et al 2013).…”
Section: Ctrc Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the CTRC variants in exons 3 and 7 are associated with CP in Europe and India (Rosendahl et al 2008;Masson et al 2008;Beer et al 2013;Paliwal et al 2013). In European cohorts, the micro-deletion variants p.K247_R254del (c.738_761del24) and p.R254W, both located in exon 7, are the most common CTRC variants (Rosendahl et al 2008;Masson et al 2008;Beer et al 2013).…”
Section: Ctrc Variantsmentioning
confidence: 99%
“…In European cohorts, the micro-deletion variants p.K247_R254del (c.738_761del24) and p.R254W, both located in exon 7, are the most common CTRC variants (Rosendahl et al 2008;Masson et al 2008;Beer et al 2013). In India, these variants are rare, and the p.A73T (c.217G>A) variant in exon 3 and the p.V251I (c.703G>A) variant in exon 7 are the most common ones (Rosendahl et al 2008;Paliwal et al 2013). These common variants in Europe and India are very rare in Japanese subjects and only one patient with idiopathic CP had the p.R254W variant (Table 5).…”
Section: Ctrc Variantsmentioning
confidence: 99%
“…However, in the presence of submillimolar calcium concentrations prevailing in pancreatic secretions, the dominant effect of CTRC is trypsinogen degradation, which is responsible for protecting the pancreas against premature, intra-pancreatic activation of trypsinogen. A number of human genetic studies indicate that loss-of-function mutations in CTRC increase the risk for chronic pancreatitis (11)(12)(13)(14)(15). Similarly, mutations in human cationic trypsinogen that inhibit CTRC-mediated degradation or accelerate CTRC-mediated cleavage of the activation peptide cause hereditary chronic pancreatitis (7).…”
Section: Human Chymotrypsin C (Ctrc)mentioning
confidence: 99%
“…[4][5][6] Although variants in cystic fibrosis transmembrane regulator (CFTR, MIM602421), chymotrypsin C (CTRC, MIM601405), and carboxypeptidase A1 (CPA1, MIM114850) predict susceptibility to CP both in Europeans and in Indians, the spectrum of mutations is different. [7][8][9][10][11] Variants in the propeptide region of cathepsin B (CTSB, MIM116810) are also associated with TCP but not replicated in Europeans. 12,13 Thus, genetic studies till date stress on the central role of intrapancreatic trypsin activity in disease pathogenesis.…”
mentioning
confidence: 98%